ASUHAN KEPERAWATAN DENGAN STUDI KASUS ISOLASI SOSIAL DENGAN PENDEKATAN CARING TEORI JEAN WATSON: Nursing Care with a Case Study of Social Isolation using Jean Watson's Caring Theory Approach - Trisusanti Yona Eva; Yanti Rosdiana; Sirli Mardiana Trishinta (Forind Press, 2023)
The recent increase in mental health problems is still a concern throughout the world. Due to waste and inefficiency, these psychological problems are caused by incompetence and deficiencies, both individually and collectively, which will hinder human and environmental growth. The purpose of contextual investigation is to find out about parenting through social contextual research using Jean Watson's Hypothetical Caring technique. The research design used is a case study. The number of clients used was three, namely social isolation clients. Social alienation is an issue raised. He received therapy from a maintenance treatment program. A third quiet patient was found to have a tendency to isolate himself indoors, was unmotivated to work with others, and spent a lot of time alone before receiving supportive care. After receiving maintenance treatment for four groups, it was found that the third patient was persistent in talking to those closest to him, was able to start a conversation, and expressed the need to cooperate. Some argue that people with social isolation can benefit from group action therapy in this way. We really hope that future authors will be willing to use a methodological approach to provide appropriate execution in order to obtain comprehensive data and make execution more effective.